2017
DOI: 10.1021/acs.inorgchem.7b02102
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Inorganic Compounds Containing Carbon, Nitrogen, and Oxygen at High Pressures

Abstract: Ternary CNO compounds are actively researched as novel high energy density and ultrahard materials. Although some synthesis work has been performed at ambient conditions, very little is known about the high pressure chemistry of of CNO compounds. In this work, first-principles variable-composition evolutionary structure prediction calculations are performed with the goal of discovering novel mixed CNO materials at ambient and high pressure conditions. By systematically searching ternary variable composition cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
3
16
2
Order By: Relevance
“…As at 500 GPa, this plane contains most stable or metastable ternary and quaternary phases. Along the edges, we find stable carbonic acid, H2CO3, ammonia hemihydrate (NH3)2 (H2O) and quarterhydrate (NH3)4 (H2O), cyanamide, CH2N2, carbon nitride imide, HC2N3, and oxycyanide, C2N2O, in agreement with literature (25,27,31). All are simple binary mixtures of the end members of this chemical subspace, forming in 1:1, 1:2, or 1:4 ratios.…”
supporting
confidence: 88%
“…As at 500 GPa, this plane contains most stable or metastable ternary and quaternary phases. Along the edges, we find stable carbonic acid, H2CO3, ammonia hemihydrate (NH3)2 (H2O) and quarterhydrate (NH3)4 (H2O), cyanamide, CH2N2, carbon nitride imide, HC2N3, and oxycyanide, C2N2O, in agreement with literature (25,27,31). All are simple binary mixtures of the end members of this chemical subspace, forming in 1:1, 1:2, or 1:4 ratios.…”
supporting
confidence: 88%
“…[8]. Several recent * dominika.melicherova@fmph.uniba.sk works investigated the possibility of creating and stabilizing single N-N bonds in systems other than pure nitrogen [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The superhardness effect was attributed to the strong electron localization into p-d orbital hybridization, induced by the N-N interstitial precompression. On the other hand, nitrogen-rich compounds have been considered as potential high-energy-density materials [16][17][18][19][20][21] . Recent theoretical predictions found that nitrogen can form rings at high pressure [19][20][21] .…”
mentioning
confidence: 99%